Lettuce growth and nutrient uptake response to winery waste compost and biochar - Pinto, Rui (2021)
The composting process of winery wastewater sludge with grape stalks enables these wastes to be recycled as soil organic amendments or pot substrate components. However, it is necessary to assess the potential of this compost as crop fertilizer. This assessment is also needed for the use of biochar as soil amendment because negative effects on crop growth and nutrient uptake may occur depending on application rates and biochar physical and chemical characteristics. With this aim, a randomized block design pot experiment with lettuce was set up with four treatments including: (i) 5% (w/w) of winery waste compost; (ii) 4% (w/w) biochar (commercial charcoal); (iii) 5% (w/w) winery waste compost with 4% (w/w) biochar; and (iv) a control treatment without soil amendments (T0). Lettuce shoot yield increased 13% with compost application but decreased 18% with biochar in comparison to T0 and 25% with compost and biochar compared to compost alone. Similarly, lettuce root weight increased with compost, but not with biochar. Lettuce shoot dry matter (DM), N and Ca contents clearly increased with compost application compared to lettuce grown in the treatment with biochar. The same happened for root Ca and Mg contents. The lowest P and K contents of lettuce shoots and roots were recorded in T0. However, lettuce root N content decreased with biochar compared to T0. Therefore, root and shoot growth and nutrient uptake decreased with soil application of 4% (w/w) of biochar whereas the winery waste compost showed positive effects as soil fertilizer.